Is Less Invasive Surfactant Administration Necessary or “Only” Helpful or Just a Fashion? - Lista, Gianluca; Bresesti, Ilia; Fabbri, Laura (American Journal of Perinatology, 2018)
In the 1990s, the most relevant pillars in the treatment of neonatal respiratory distress syndrome (RDS) have been improvements in ventilation strategies, the introduction of exogenous surfactant replacement therapy, and the use of antenatal steroids. Lately, in addition to the standard INSURE (INtubation–SURfactant administration–Extubation) method to administer surfactant, a new technique has been gaining increasing popularity. It is the so-called less invasive surfactant administration (LISA) method, which has shown promising results in preventing bronchopulmonary dysplasia development and in reducing mortality in preterm neonates. The rationale behind this technique is to avoid positive pressure ventilation and the endotracheal tube, being surfactant delivered through a thin catheter while the neonate is maintained on continuous positive airway pressure. Given the paucity of large-scale randomized trials on LISA method to prove its effects on short- and long-term outcomes, some questions still remain unanswered. Then, uncertainty regarding the feasibility of this maneuver needs to be better clarified before gaining wide acceptance in routine clinical practice. In our report, we aim at hypothesizing the main mechanisms behind the efficacy of LISA, considering it as a single maneuver in a comprehensive approach for RDS management in the delivery room.
Keywords: surfactant administration; LISA technique; preterm infants; noninvasive respiratory support